The Benefit of Alum in Tonsillectomy - Ahmed M. Al-Abbasi (Gomal Journal of Medical Sciences, 2009)
Background: Tonsillectomy is one of the frequent operations performed by Otolaryngologists world over. Otolaryngologists are in search of a technique of tonsillectomy where the operation time and operative blood loss is less. This study was carried out to evaluate the effect of aluminium potassium sulfate on tonsillectomy time, blood loss during the surgery and the number of ties used.